Bit-Communication In Artifical Swarm - Jaafar, Anuar; Othman, N.F.; Zainuddin, Muhammad Noorazlan Shah; Ismail, Mohd Muzafar; Mahmud, Mohd Nazri (2012)
Bit communication in swarm agents is a communication process of transmitting data within specific area. The data must be delivered to all agents in the area which this process also closely related to broadcasting manner through bit-communication as a way to spread out the data among all those agents. This research field is supposed to have a deep study of behavior of homogeneous agents by inspecting the reversing and non-reversing approach. It also included the investigation of the independent and characteristic of transmitting and receiving data for random process of swarm. In this paper, swarm technique is implemented which is useful for bit-communication behavior. There are two approaches are used for transmitting and receiving process. For the reverse approach, the data can be resend back to the sender for the next cycle where the program randomly select one-of nearest agent for transmitting the data. While in non-reversing approach, the data cannot retransmit back to the sender in the previous cycle; this approach may increase the system performance and efficiency.